ANALISIS USAHATANI TANAMAN TOMAT (Solanum Lycopersium) DI KEBUN PRAKTEK FAKULTAS TEKNOLOGI PANGAN PERTANIAN DAN PERIKANAN UNIVERSITAS NUSA NIPA - Achmad Robbi; Yohana Anggriani; Taras Iawan Saputera Wanda (Jurnal Biogenerasi, 2026)
Tomato farming (Solanum lycopersicum) is one of the horticultural activities with considerable economic potential; however, it also faces challenges such as high production costs, cultivation risks, and price fluctuations. This study aims to analyze production costs, revenue, income, and financial feasibility of tomato farming conducted at the Practice Garden of the Faculty of Food Technology, Agriculture, and Fisheries, Nusa Nipa University, Indonesia. A descriptive quantitative approach was employed, using primary data obtained from direct observation and systematic recording during the farming activities, as well as secondary data from relevant institutional reports and literature.The results indicate that the total production cost of tomato farming amounted to IDR 5,728,664, while total revenue reached IDR 6,000,000, resulting in a net income of IDR 271,336 per planting season. Financial feasibility analysis using the Revenue-Cost (R/C) Ratio yielded a value of 1.05, indicating that the tomato farming enterprise is economically feasible and profitable. Therefore, tomato farming at the practice garden has the potential to be further developed, particularly through improved efficiency in input utilization and better cost management. This study is expected to serve as a reference for students, farm managers, and farmers in making informed decisions regarding sustainable horticultural farming practices.